STANDAR JALAN YANG BERWAWASAN KESELAMATAN TRANSPORTASI DARAT - Hikmat Iskandar (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
The vital role of roads in supporting community activities is needed to be maintained consistently and incessantly, so roads are able to perform as its standard. Road standard is a term of reference for developing land transportation infrastructure, defined by minimum criteria for accommodating vehicle’s dimension and c haracteristics so that any trip using roads can be done safely, fast, economist or a ffordable by any level of community, and comfortable. The article discusses Road Standard stipulated in Regulations Related to Roads and their use accompanied by government Regulations and technical guidance. According to Regulations, standard of road usage must be obeyed and as a reference for traffic authorities, and therefore, physical performance of roads must be standardized. This paper aims to discuss road standard as it is stated by the law related to road as infrastructure for road transportation and its utilization,including government regulation and other derived regulations. As it is stated in the Roads Law and Traffic & roads transportation law, road standard and its utilization govern institutions responsible for it have to followed as minimum standard to fulfill safety for road users. Two specifications are explained in this paper. Key word: Road Geometric, Road standard, safety.